Identification of paternal uniparental disomy on chromosome 22 and a de novo deletion on chromosome 18 in individuals with orofacial clefts. Issue 6 (23rd August 2018) - Oseni, Ganiyu O.; Jain, Deepti; Mossey, Peter A.; Busch, Tamara D.; Gowans, Lord J.J.; Eshete, Mekonen A.; Adeyemo, Wasiu L.; Laurie, Cecelia A.; Laurie, Cathy C.; Owais, Arwa; Olaitan, Peter B.; Aregbesola, Babatunde S.; et al.
Abstract: Background: Orofacial clefts are the most common malformations of the head and neck region. Genetic and environmental factors have been implicated in the etiology of these traits. Methods: We recently conducted genotyping of individuals from the African population using the multiethnic genotyping array (MEGA) to identify common genetic variation associated with nonsyndromic orofacial clefts. The data cleaning of this dataset allowed for screening of annotated sex versus genetic sex, confirmation of identify by descent and identification of large chromosomal anomalies. Results: We identified the first reported orofacial cleft case associated with paternal uniparental disomy (patUPD) on chromosome 22. We also identified a de novo deletion on chromosome 18. In addition to chromosomal anomalies, we identified cases with molecular karyotypes suggesting Klinefelter syndrome, Turner syndrome and Triple X syndrome. Conclusion: Observations from our study support the need for genetic testing when clinically indicated in order to exclude chromosomal anomalies associated with clefting. The identification of these chromosomal anomalies and sex aneuploidies is important in genetic counseling for families that are at risk. Clinicians should share any identified genetic findings and place them in context for the families during routine clinical visits and evaluations. Abstract : The de novo deletion identified is novel and would be of interest to the orofacial clefts community as we continue to identify the causes of clefts. This study will add to the growing list of genetics studies for orofacial clefts in the African population which hitherto has been limited. Knowledge gained from this study can be translated to other populations.